ROBUST OPTIMIZATION DESIGN OF SUSPENSION BASED ON 6σ - FENG JinZhi; YANG ZhiFeng; YANG ZhenYi; LIN Yang; ZHENG SongLin (Jixie qiangdu)
In actual production,the key components of the suspension such as the stabilizer bar,the rubber bushing and the spring are unstable due to the unstable manufacturing process,which greatly affects the vehicles’ smoothness and stability. In this paper,the McPherson front suspension is used as the research carrier,the stiffness characteristics of the components are taken as the noise variable,the hard point coordinate value is taken as the design variable,and the high-precision approximate model is established by the quadratic response surface method. Based on the same constraints, the sequence quadratic optimization algorithm is used to deterministic optimize of the suspension and the robustness design of it. The Monte Carlo simulation is used to analyze the robustness of each optimization result. The results show that the 6σ-based robustness optimization design not only optimizes the performance of the suspension but also has an advantage in terms of reliability.